Health Risks of Nitrogen Dioxide Exposure Among Primary School Children in Ogan Ilir, South Sumatra, Indonesia: Effect on Lung Function (Association of Public Health Scholars based in Faculty of Public Health, Sriwijaya University, 2020)
Nitrogen dioxide (NO2) is one of the most dangerous air pollutants as regards human health. Increased traffic volumes on the east-lane roadside of South Sumatra have led to increased NO2 concentrations. In terms of age and NO2, children are the greatest risk group. The aim of this research was to estimate health risks of NO2 and analyze the correlation between exposure and lung capacity. This was an analytical study, with a cross-sectional design and risk analysis. The study group consisted of 100 children of primary school age. The results showed that the noncancer hazard index (HI)for NO2 exposure based on real-time data was 1.138. In the study population, as shown by the noncancer HI, 22% of students in OganIlir were classified as not at risk (HI < 1), whereas 78% were classified as at risk (HI ≥ 1). According to the results of simple linear regression, FEV1 (Pearson’s test: 0.0001) and FVC (Pearson’s test: 0.0001) showed a significant correlation with noncancer NO2 risk. The results of simulations suggested that a value of 0.176 mg/m3 can be used as a quality standard recommendation (health advisory) for NO2 exposure in roadside schools, especially schools abutting inter-provincial roads in South Sumatra